2018
DOI: 10.1016/s2468-2667(18)30144-0
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality risk associated with long-term exposure to ambient PM2·5 in China: a cohort study

Abstract: Background Evidence from cohort studies in North America and Europe indicates that long-term exposure to fine particulate matter (PM₂ • ₅) is associated with an increased mortality risk. However, this association has rarely been quantified at higher ambient concentrations. We estimated the hazard ratio (HR) for all-cause mortality from longterm exposure to PM₂ • ₅ in a well established Chinese cohort of older adults. Methods The Chinese Longitudinal Healthy Longevity Survey (CLHLS) is a prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
158
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 233 publications
(179 citation statements)
references
References 32 publications
18
158
3
Order By: Relevance
“…Annual PM 2•5 estimates were calculated from 1998 to 2014, at 1 km² spatial resolution, which was the longest and the highest resolution exposure dataset available. 7 Additionally, our estimations were highly consistent with out-of-sample cross-validated concentrations from monitors (R²=0•81) and another exposure dataset (R²=0•81) in China. 7 A previous study 7 found that 3-year average PM 2•5 before death or the end of the study had the strongest association with mortality.…”
Section: Implications Of All the Available Evidencesupporting
confidence: 74%
See 1 more Smart Citation
“…Annual PM 2•5 estimates were calculated from 1998 to 2014, at 1 km² spatial resolution, which was the longest and the highest resolution exposure dataset available. 7 Additionally, our estimations were highly consistent with out-of-sample cross-validated concentrations from monitors (R²=0•81) and another exposure dataset (R²=0•81) in China. 7 A previous study 7 found that 3-year average PM 2•5 before death or the end of the study had the strongest association with mortality.…”
Section: Implications Of All the Available Evidencesupporting
confidence: 74%
“…[3][4][5][6] A study using the Chinese Longitudinal Healthy Longevity Survey (CLHLS) reported that each 10 µg/m³ increase in the past 3-year average PM 2•5 was associated with 8% higher mortality in adults aged 65 years or older, and extrapolated that 1 765 820 premature deaths among Chinese older adults were caused by ambient air pollution. 7 Since 2008, China has made efforts towards controlling air pollution. However, these efforts might be offset by urbanisation, which has intensified the health effects of air pollution as people move from rural areas with lower ambient air pollution into urban areas with higher ambient air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…It combines remote sensing from National Aeronautics and Space Administration's Moderate Resolution Imaging Spectroradiometer, Multiangle Imaging Spectroradiometers, and Sea-viewing Wide eld-of-view Sensor satellite instruments; vertical pro les derived from the GEOS-Chem chemical transport model; and calibration to ground-based observations of PM 2.5 using geographically weighted regression. Annual PM 2.5 estimates were calculated from 2000 to 2014, at 1 km x 1 km spatial resolution, which was the longest and the highest resolution exposure dataset available [33,34]. Additionally, our estimations were highly consistent with out-of-sample crossvalidated concentrations from monitors (R²=0•81) and another exposure dataset in China (R²=0•79) [32].…”
Section: Methodssupporting
confidence: 58%
“…In order to avoid the bias and data deficiency caused by using ground monitoring data and improve the accuracy of calculation results, we use PM 2.5 concentration data based on satellite remote sensing [27,28]. In general, the data can effectively measure the average level of air pollution in a certain region [29].…”
Section: Data Sourcesmentioning
confidence: 99%